2022
DOI: 10.1021/jacs.2c07297
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective and Diastereodivergent Allylation of Propargylic C–H Bonds

Abstract: An iridium-catalyzed stereoselective coupling of allylic ethers and alkynes to generate 3,4-substituted 1,5-enynes is reported. Under optimized conditions, the coupling products are formed with excellent regio-, diastereo-, and enantioselectivities, and the protocol is functional group tolerant. Moreover, we report conditions that allow the reaction to proceed with complete reversal of diastereoselectivity. Mechanistic studies are consistent with an unprecedented dual role for the iridium catalyst, enabling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…We posited that a π ‐complexation‐assisted deprotonation strategy for the generation of a chiral allenylmetal reagent from an alkyne (Scheme 1B, top left) could enable the desired reactivity [9] . Liming Zhang and co‐workers previously demonstrated the utility of this approach using bifunctional Au/Brønsted base catalysts for intramolecular coupling of alkyne and aldehydes, [10] while more recently, our group reported an intermolecular propargylic allylation in the presence of an Ir catalyst (Scheme 1B, bottom left) [11] . The successful development of this highly stereo‐ and regioselective system for propargylic C−H allylation using allylic ethers as allylic cation equivalents led us to explore the feasibility using other easily accessible electrophilic reagents for introducing heteroatom‐based functional groups (Scheme 1B, right).…”
Section: Introductionmentioning
confidence: 98%
“…We posited that a π ‐complexation‐assisted deprotonation strategy for the generation of a chiral allenylmetal reagent from an alkyne (Scheme 1B, top left) could enable the desired reactivity [9] . Liming Zhang and co‐workers previously demonstrated the utility of this approach using bifunctional Au/Brønsted base catalysts for intramolecular coupling of alkyne and aldehydes, [10] while more recently, our group reported an intermolecular propargylic allylation in the presence of an Ir catalyst (Scheme 1B, bottom left) [11] . The successful development of this highly stereo‐ and regioselective system for propargylic C−H allylation using allylic ethers as allylic cation equivalents led us to explore the feasibility using other easily accessible electrophilic reagents for introducing heteroatom‐based functional groups (Scheme 1B, right).…”
Section: Introductionmentioning
confidence: 98%
“…[9] Liming Zhang and coworkers previously demonstrated the utility of this approach using bifunctional Au/Brønsted base catalysts for intramolecular coupling of alkyne and aldehydes, [10] while more recently, our group reported an intermolecular propargylic allylation in the presence of an Ir catalyst (Scheme 1B, bottom left). [11] The successful development of this highly stereo-and regioselective system for propargylic CÀ H allylation using allylic ethers as allylic cation equivalents led us to explore the feasibility using other easily accessible electrophilic reagents for introducing heteroatom-based functional groups (Scheme 1B, right).…”
Section: Introductionmentioning
confidence: 99%
“…Our group and others have shown that coordination of a cationic late transition metal complex to a C-C p-bond can greatly enhance the C-H acidity of the neighboring allylic, propargylic, or allenic protons. 26,27 In particular, through the use of cyclopentadienyliron(II) dicarbonyl derivatives as catalysts, 28 this acidity enhancement enables the use of weak, functional group-tolerant amine bases to effect the allylic deprotonation of olens to generate nucleophilic allyliron intermediates that react with electrophiles with S E 2 0 selectivity. [29][30][31][32][33][34][35] We further discovered that these nucleophilic organoiron species will undergo electrophilic functionalization with chalcone derivatives through a 1,4-addition process.…”
Section: Introductionmentioning
confidence: 99%